E-COMMERCE DAN ETIKA BERTRANSAKSI DALAM PRESFEKTIF HUKUM EKONOMI ISLAM - Jumasrah; Amriati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study explores transactional ethics in e-commerce from the perspective of Islamic Economic Law. Using a literature-based approach, the research examines key Sharia principles such as contract clarity, honesty, fairness, and the prohibition of gharar and fraud within digital transactions. The findings indicate that e-commerce is fundamentally permissible as long as contract conditions are fulfilled and transparency is maintained between sellers and buyers. The study emphasizes the importance of applying Islamic ethical values to reduce fraudulent behavior, strengthen consumer protection, and ensure safer and more reliable digital transactions.